Toxic Optic Neuropathy Due to Metanol in Dr. Sardjito Hospital (Lapen Intoxication) Case Series - Bellarinatasari, Nika; Hartono, Hartono (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2011)
Purpose: To describe three cases of toxic optic neuropathy due to methanol.Method: Case seriesResults: There were 3 cases in Dr. Sardjito Hospital. First case, a male, 28 years old, drunk three glasses of lapen about 1 week before he went to hospital. At his first time he came, his vision was no light perception (NLP) for both eyes. Then he hospitalized for a week and got 48 mg methyl prednisolone orally. After 1 month, his vision of the both eyes didn’t improve. From the sample of his drink, we found methanol 4,38% and ethanol 4,91%. Second case, a male, 46 years old, drunk one glass of lapen about 4 days before he went to hospital. His vision was NLP for both eyes. Like the first case, he got the same management, and after 1 month his vision still didn’t improve. From the sample of his drink, we found methanol 12,41% and ethanol 3,74%. Third case, a male, 21 years old, drunk more than 3 glasses of combination of Vodka, lapen, Kratingdaeng, and beer. The visual acuity were 3/60 for the right eye and hand movement (HM) for the left eye. Like the cases before, he got the same management, and after 1 month his vision had improved became 3/60 for the right eye and 2,5/60 for the left eye. Unfortunately, we didn’t have the sample of his drink.Conclusion: Lapen is Yogyakarta home made beverage which contains with methanol. Methanol is toxic liquid that cause toxic optic neuropathy. Blindness is the most common symptom and permanent (Sains Medika, 3(2):177-184).